Safety of Coadministration of Continuous Infusions of Propofol and Clevidipine: A Multi‐Site Retrospective Analysis - Micaela N. Warfield; Kristin C. Cole; Kiyan Heybati; Nicholas J. Vollmer; Erin D. Wieruszewski; Hemang Yadav; Alejandro A. Rabinstein; Caitlin S. Brown (Pharmacotherapy: The Journal of Human Pharmacology and Drug Therapy, 2026)
ABSTRACT Introduction Patients often receive propofol for sedation and clevidipine for hypertension in the intensive care unit. Both agents are formulated as a lipid emulsion, which may increase the risk of hypertriglyceridemia and acute pancreatitis with their coadministration. We aimed to determine the incidence of hypertriglyceridemia and acute pancreatitis with concurrent administration of propofol and clevidipine and identify patient risk factors for hypertriglyceridemia. Methods This was a multicenter retrospective study of adult patients (≥ 18 years old) receiving concurrent propofol and clevidipine infusions for ≥ 6 h. The primary outcome was the frequency of triglyceride levels greater than 400 mg/dL and acute pancreatitis. The secondary outcome was risk factors associated with hypertriglyceridemia during concurrent propofol and clevidipine infusions until both infusions had been discontinued. Univariable and multivariable logistic regression analyses were used to assess risk factors of hypertriglyceridemia in patients receiving concurrent propofol and clevidipine infusions. Results Across 1,226 patients, the median duration of infusion overlap was 12.4 [interquartile range (IQR) 8.3, 22.7] hours. The mean age of the cohort was 59.6 [standard deviation (SD) 14.9] years, and 59.4% were male. Assuming those without a triglyceride level drawn did not have hypertriglyceridemia, hypertriglyceridemia after initiation of propofol and clevidipine infusion was found in 7.7% [95% confidence interval (CI) 6.3% to 9.3%] of the entire cohort. Twenty‐six patients (2.1%) had a diagnosis of pancreatitis after initiation of lipid infusions, of which 12 cases were possibly infusion‐related, and one case was likely infusion‐related. After calculating the Naranjo Scale, all 13 cases of pancreatitis were possibly related to propofol or clevidipine infusions. Based on a multivariable logistic regression of those with a triglyceride level available, risk factors for hypertriglyceridemia included pancreatitis within the past 5 years [adjusted odds ratio (aOR) 2.77, 95% CI, 1.23 to 6.23] and statin use (aOR 1.94, 95% CI, 1.13 to 3.34). Conclusions In our cohort of patients receiving concurrent propofol and clevidipine, the frequency of hypertriglyceridemia and acute pancreatitis was low. Further comparative studies are warranted to assess the risk of pancreatitis with the addition of clevidipine to propofol.